Equipping immigrants: migration flows and capital movements - Fabian Lange; Douglas Gollin (Institute for the Study of Labor (IZA), 2007)
Both policy makers and researchers have devoted considerable attention in recent years to the large current account and capital account imbalances among OECD countries. In particular, the size of the United States current account deficit has attracted intense attention and spawned numerous explanations. There are undoubtedly many reasons for this deficit, including government fiscal policy imbalances, but one explanation that has not previously received much attention is that current account deficits and the matching capital inflows are responses to international flows of labor. Migrants must be equipped with machines, and the resulting demands for capital are likely, all else being equal, to generate cross-border flows of capital. This paper explores the extent to which migration-related capital flows can explain the movements and magnitudes of current and capital account imbalances in OECD countries.
urn:nbn:de:101:1-20080402297
Keywords: 330; Internationale Wanderung; Kapitalmobilität; Zahlungsbilanzungleichgewicht; Leistungsbilanz; Kapitalbilanz; OECD-Staaten